Community land in Kenya: Policy making, social mobilization, and struggle over legal entitlement - Francesca Di Matteo (London School of Economics and Political Science (LSE), Department of International Development, 2017)
Stemming from colonial legacy, independent Kenya failed to recognize customary interests in land as possessing force as statutory derived rights. This lies at the heart of the so-called "land question" in Kenya. Moreover, issues related to land rights are perceived as the root causes of conflicts occurring in the 1990s and 2000s. As a result of a crisis recovery process, the 2010 Constitution has embodied the fundaments of land reforms; it has acknowledged "communities" as legally entitled to hold land. The present paper studies decision-making processes via a socio-anthropological approach showing how it contributes to understanding the issues at stake in the reform of Kenya's land tenure system, and the politics surrounding the design of new legislation around "community land". Through the analysis of interlocking of scales of governance, the paper documents the manner in which local actors participate in, interpret, divert, or exploit policy debates undergoing at the national level.
Keywords: 330; Community; land reform; Kenya; policy process; actors agency; land poltics